The Effect of the Root Bark of Lycium chinense (Lycii Radicis Cortex) on Experimental Periodontitis and Alveolar Bone Loss in Sprague-Dawley Rats - Jinwon Yang; Hyosun Song; Jeongjun Lee; Hunsuk Chung; Young-Sam Kwon; Kyung-Hwan Jegal; Jae-Kwang Kim; Sae-Kwang Ku (MDPI AG, 2024)
Lycii Radicis Cortex (LRC), the dried root bark of Lycium chinese Mill., has traditionally been used as a medicinal herb in East Asia to treat fever and hyperhidrosis. In the present study, we investigated the effects of LRC extract on ligation-induced experimental periodontitis and associated alveolar bone loss in rats. Twenty-four hours after ligation placement, LRC was orally administered once daily for 10 days. Firstly, LRC administration inhibited anaerobic bacterial proliferation and inflammatory cell infiltration in gingival tissues. Additionally, LRC exhibited anti-inflammatory effects by reducing the expression of inflammatory mediators, including prostaglandin E2, interleukin-1β, and tumor necrosis factor-α. LRC treatment also downregulated mRNA expression of these inflammatory mediators in lipopolysaccharide-stimulated RAW 264.7 cells by inhibiting the mitogen-activated protein kinases and nuclear factor-κB (NF-κB) signaling pathways. Furthermore, LRC showed an antioxidant effect by decreasing the malondialdehyde level and inducible nitric oxide synthase activity in gingival tissues. Moreover, LRC effectively prevented the connective tissue degradation by inhibiting matrix metalloproteinase-8 expression and the loss of collagen-occupied areas in gingival tissues. LRC also decreased the receptor activator of NF-κB ligand/osteoprotegerin (RANKL/OPG) ratio, as well as the number and occupied areas of osteoclasts on the alveolar bone surface, thereby inhibiting alveolar bone loss. In summary, these findings suggest that LRC is a promising medicinal herb for alleviating periodontitis and related alveolar bone loss through its antimicrobial, anti-inflammatory, and antioxidant properties.